Pigs immunized with Chinese highly pathogenic PRRS virus modified live vaccine are protected from challenge with North American PRRSV strain NADC-20. Issue 30 (9th July 2015) - Galliher-Beckley, Amy; Li, Xiangdong; Bates, John T.; Madera, Rachel; Waters, Andrew; Nietfeld, Jerome; Henningson, Jamie; He, Dongsheng; Feng, Wenhai; Chen, Ruiai; Shi, Jishu
Highlights: We found that JXA-1R MLV vaccine can protect pigs from HP-PRRSV challenge in a U.S. setting. We also found that JXA-1R can protect pigs from NA circulating PRRSV NADC-20 challenge. Protection may be due to JXA-1R-induced broadly neutralizing antibodies and enhanced pulmonary IFN-α/β production. Abstract: Modified live virus (MLV) vaccines developed to protect against PRRSV circulating in North America (NA) offer limited protection to highly pathogenic (HP) PRRSV strains that are emerging in Asia. MLV vaccines specific to HP-PRRSV strains commercially available in China provide protection to HP-PRRSV; however, the efficacy of these HP-PRRSV vaccines to current circulating NA PRRS viruses has not been reported. The aim of this study is to investigate whether pigs vaccinated with attenuated Chinese HP-PRRSV vaccine (JXA1-R) are protected from infection by NA PRRSV strain NADC-20. We found that pigs vaccinated with JXA1-R were protected from challenges with HV-PRRSV or NADC-20 as shown by fewer days of clinical fever, reduced lung pathology scores, and lower PRRS virus load in the blood. PRRSV-specific antibodies, as measured by IDEXX ELISA, appeared one week after vaccination and virus neutralizing antibodies were detected four weeks post vaccination. Pigs vaccinated with JXA1-R developed broadly neutralizing antibodies with high titers to NADC-20, JXA1-R, and HV-PRRSV. In addition, we also found that IFN-α and IFN-β occurred at higher levels in the lungs of pigs vaccinated with JXA1-R. Taken together, our studies provide the first evidence that JXA1-R can confer protection in pigs against the heterologous NA PRRSV strain NADC-20.